Arabidopsis histone demethylases LDL1 and LDL2 control primary seed dormancy by regulating DELAY OF GERMINATION 1 and ABA signaling-related genes - Zhao, Minglei; Yang, Songguang; Liu, Xuncheng; Wu, Keqiang (Frontiers in Plant Science, 2015)
Seed dormancy controls germination and plays a critical role in regulating the beginning of the life cycle of plants. Seed dormancy is established and maintained during seed maturation and is gradually broken during dry storage (after-ripening). The plant hormone abscisic acid (ABA) and DELAY OF GERMINATION1 (DOG1) protein are essential regulators of seed dormancy. Recent studies revealed that chromatin modifications are also involved in the transcription regulation of seed dormancy. Here, we showed that two Arabidopsis histone demethylases, LYSINESPECIFIC DEMETHYLASE LIKE 1 and 2 (LDL1 and LDL2) act redundantly in repressing of seed dormancy. LDL1 and LDL2 are highly expressed in the early silique developing stage. The ldl1 ldl2 double mutant displays increased seed dormancy, whereas overexpression of LDL1 or LDL2 in Arabidopsis causes reduced dormancy. Furthermore, we showed that LDL1 and LDL2 repress the expression of seed dormancy-related genes, including DOG1, ABA2 and ABI3 during seed dormancy establishment. Furthermore, genetic analysis revealed that the repression of seed dormancy by LDL1 and LDL2 requires DOG1, ABA2 and ABI3. Taken together, our findings revealed that LDL1 and LDL2 play an essential role in seed dormancy.